The implementation of the students experiment learning method to improve science learning outcomes on the topic of living beings and their environment in fourth grade of madrasah ibtidaiyah - Nisa Auliya; Lailla Hidayatul Amin; Muhammad Fatchurrohman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to: (1) determine the implementation of the Students Experiment learning method in Science subjects, specifically on the topic of living beings and their environment in the fourth grade of MI Muhammadiyah Sidokerto; (2) assess whether the use of the Students Experiment method can improve students' learning outcomes in the fourth grade of MI Muhammadiyah Sidokerto. The research design used is Classroom Action Research (CAR), which aims to solve a particular problem and present the results in a comprehensive description. The subjects of this CAR study are fourth-grade students of MI Muhammadiyah Sidokerto. This study consists of two cycles, namely Cycle I and Cycle II, where each cycle comprises four stages: planning, implementation, observation, and reflection. The research findings are as follows: The implementation of the Students Experiment learning method in Science subjects on the topic of living beings and their environment in the fourth grade of MI Muhammadiyah Sidokerto, involving 30 students, was carried out by the teacher explaining the steps students needed to follow. Then, students were asked to observe the growth process of plants and later present their observations in front of the class. The implementation of the Students Experiment learning method in Science subjects on the topic of living beings and their environment for fourth-grade students of MI Muhammadiyah Sidokerto was proven to improve learning outcomes. This improvement was evidenced by the increase in learning outcomes from Cycle I to Cycle II compared to the pre-cycle phase. In the pre-cycle phase, the average learning outcome score was only 64.00. In Cycle I, the average learning outcome increased to 71.10, and in Cycle II, it further improved to 77.16. The number of students who met the Minimum Mastery Criteria (KKTP) (>70) in the pre-cycle phase was only 10 students or 33%. In Cycle I, this number increased to 18 students or 60%, and in Cycle II, it further rose to 27 students or 83%. The improvement in learning outcomes from the pre-cycle phase to Cycle II indicates that students have successfully reached the KKTP (>70) and achieved the performance indicator (>75%) targeted by the researcher.